Hepatocarcinoma. Hemoperitoneum - Chifflet, Juan; Cassinelli, Daniel; Toledo, Nancy (Cirugía del Uruguay, 1974)
Description of a case of primitive liver carcinoma includes clinical aspects, appearance of non cirrhotic liver, presence of hemoperitoneum and multicentric appearance of tumor.